2016
DOI: 10.3389/fphys.2016.00359
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Functional Specialization along the Intestinal Tract of a Carnivorous Teleostean Fish (Dicentrarchus labrax)

Abstract: High-quality sequencing reads from the intestine of European sea bass were assembled, annotated by similarity against protein reference databases and combined with nucleotide sequences from public and private databases. After redundancy filtering, 24,906 non-redundant annotated sequences encoding 15,367 different gene descriptions were obtained. These annotated sequences were used to design a custom, high-density oligo-microarray (8 × 15 K) for the transcriptomic profiling of anterior (AI), middle (MI), and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 105 publications
2
28
0
Order By: Relevance
“…Absorption of lipids occurs mostly in the first segments of fish intestines, where bile salts are secreted to hydrolyze triglycerides to free fatty-acids and glycerol ( Sundell & Rønnestad, 2011 ) resembling mammalian small intestines. In accordance, expression of fabp6 , involved in reabsorption of bile acids and exclusively expressed in mammalian ileums ( Besnard et al, 2002 ), can only be found in the posterior intestinal segment of GSB and other fish species ( Alves-Costa et al, 2008 ; Pérez-Sánchez et al, 2015 ; Calduch-Giner, Sitjà-Bobadilla & Pérez-Sánchez 2016 ). FABP2, involved in regulation of the intracellular concentration of free fatty acids, preferentially binds long-chain fatty acids (LCFAs) ( Lowe et al, 1987 ), but can also bind MCFAs ( Huang et al, 2002 ).…”
Section: Discussionmentioning
confidence: 82%
“…Absorption of lipids occurs mostly in the first segments of fish intestines, where bile salts are secreted to hydrolyze triglycerides to free fatty-acids and glycerol ( Sundell & Rønnestad, 2011 ) resembling mammalian small intestines. In accordance, expression of fabp6 , involved in reabsorption of bile acids and exclusively expressed in mammalian ileums ( Besnard et al, 2002 ), can only be found in the posterior intestinal segment of GSB and other fish species ( Alves-Costa et al, 2008 ; Pérez-Sánchez et al, 2015 ; Calduch-Giner, Sitjà-Bobadilla & Pérez-Sánchez 2016 ). FABP2, involved in regulation of the intracellular concentration of free fatty acids, preferentially binds long-chain fatty acids (LCFAs) ( Lowe et al, 1987 ), but can also bind MCFAs ( Huang et al, 2002 ).…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, over 1,900 DEGs (fold-change cutoff of 2) were observed between anterior-middle and posterior-intestinal segments (including the rectum) in a carnivorous fish, European sea bass ( Dicentrarchus labrax ) using a custom oligo microarray. 58 Using a cluster analysis of the DEGs, we extracted expression patterns that are characteristic of the three tissue types ( Supplementary Fig. S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Calduch-Giner et al 58 suggested that fish intestine transcriptomes are not static, but change spatially, seasonally and with diet. Since the samples of GI tract examined were obtained from cultured yellowtail maintained under the same conditions and sampled at the same time, our study suggests that the expression of proteolytic enzymes also varies between individuals, and that such differences may cause different physiological conditions in individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Apolipoproteins are vital in lipid transport and uptake in vertebrates and has been shown to be synthesized primarily in the intestine and liver of most teleost. As a caveat, it has been suggested that the fish intestine transcriptomes are plastic, in which they can change spatially, seasonally, and with diet (Calduch-Giner et al 2016). This provides a key detail of matching the available digestive enzymes present within the aquaculture species with the corresponding diet presented.…”
Section: Nutrition and Growthmentioning
confidence: 99%